Antonin Scalia and American constitutionalism the historical significance of a judicial icon - Purcell, Edward A. (Oxford University Press, 2020)
Antonin Scalia and American Constitutionalism is a critical study of Justice Antonin Scalia's jurisprudence, his work on the U.S. Supreme Court, and his significance for an understanding of American constitutionalism. After tracing Scalia's emergence as a hero of the political right and his opposition to many of the decisions of the Warren Court, this book examines his general jurisprudential theory of originalism and textualism, arguing that he failed to produce either the objective method he claimed or the "correct" constitutional results he promised. Focusing on his judicial performance over his thirty years on the Court, the book examines his opinions on virtually all of the constitutional issues he addressed, from fundamentals of structure to most major constitutional provisions. The book argues that Scalia applied his jurisprudential theories in inconsistent ways and often ignored, twisted, or abandoned the interpretive methods he proclaimed, in most cases reaching results that were consistent with "conservative" politics and the ideology of the post-Reagan Republican Party. Most broadly, it argues that Scalia's jurisprudence and career are particularly significant because they exemplify-contrary to his own persistent claims-three paramount characteristics of American constitutionalism: the inherent inadequacy of "originalism" and other formal interpretive methodologies to produce "correct" answers to controverted constitutional questions; the relationship-particularly close in Scalia's case-between constitutional interpretations on one hand and substantive personal and political goals on the other; and the truly and unavoidably "living" nature of American constitutionalism itself. As a historical matter, the book concludes, Scalia stands as a towering figure of irony because his judicial career disproved the central claims of his own jurisprudence"--